KOMPETENSI SOSIAL KEPALA SEKOLAH TERHADAP KUALITAS KEHIDUPAN KERJA GURU DI SMP SWASTA TERAKREDITASI A SE- KECAMATAN PAMIJAHAN BOGOR - Lestari, Hana; Rahmawati, Ima; Wahidatul Asna, Neneng (JURNAL KAJIAN ISLAM MODERN, 2023)
This research was conducted to test the hypothesis whether there is an influence between the social competence of school principals on the quality of work life of teachers in A-accredited private junior high schools in Pamijahan District, Bogor. This research uses a quantitative survey. The sample consisted of 33 teachers. The data used is secondary and primary data obtained from questionnaire results and processed using simple regression statistics. Based on the regression test, a significance value of 0.001 < 0.05 was obtained, so it can be concluded that there is a positive and significant influence between the social competence of school principals on the quality of teachers' work life